The relationship between e-cigarette use and lung disease: an integrative review (Research, Society and Development, 2022)
Electronic cigarettes (EC) have been considered by young people and adults a new form of leisure and also an alternative to replace conventional cigarettes and, because of that, they have drawn the attention of several industries for their manufacture. However, little is known yet about its real harm. The aim of this work was to describe the relationship between the consumption of electronic cigarettes and lung diseases. The present study is presented as an integrative literature review of a basic descriptive and qualitative nature. Many authors believe that electronic cigarettes are able to gradually replace conventional cigarettes, as their harm is less. However, other scientists believe that its harms are diverse and that its potential harmfulness is unknown, as its real effects under exposure and its complex structure are not yet known in depth, mainly due to the possibilities in the manufacture of e-liquids. Several authors have already warned about the risks to the lung, especially in relation to EVALI and its manifestations, believing that FB can even lead users to death. From a legislative point of view, its marketing and advertising are still prohibited. More research is needed in order to understand the background about its consequences, limits of the constitution of the e-liquid, user characteristics and usage policies.